Description of the last instar larva of Anacroneuria tucuman Stark (Plecoptera: Perlidae) from northern Argentina - Pessacq, Pablo; Marcela, de Paul A. (Zootaxa, 2015)
The last instar larva of Anacroneuria tucuman Stark is described based on material from the Yungas Forest in Jujuy Province, Argentina. This is the first record of the species for the Province.